Analyzing the Effectiveness of Village Fund Utilization in Mengkait Village, South Siantan, Anambas Islands Regency - Marco Marco; Ika Devy Pramudiana; Sapto Pramono (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to analyze the effectiveness of the use of Village Funds in Mengkait Village, South Siantan District, Anambas Islands Regency, Riau Islands Province. The Village Fund is a strategic policy of the government in order to accelerate the development and empowerment of village communities, so it is necessary to evaluate the extent to which the funds are used appropriately and effectively. The research approach used is qualitative descriptive with data collection techniques through in-depth interviews, observations, and documentation of informants consisting of village officials, community leaders, and beneficiary communities. This study uses four indicators of effectiveness, namely accuracy of timing, accuracy of cost calculation, accuracy in measurement, and accuracy in thinking. The results of the study show that the use of Village Funds in Mengkait Village in general has been quite effective. The timeliness of the implementation was largely achieved, although some activities experienced delays due to weather and logistical factors. In terms of cost calculation, the village government has prepared the budget in a participatory and transparent manner, although there have been some adjustments due to price changes in the field. Accuracy in measurements shows that physical activities have been carried out in accordance with the technical plan, although there is still a need for increased supervision and accuracy in implementation. Meanwhile, precision in thinking is reflected in program planning that starts to be based on data and the real needs of the community, although not completely visionary or long-term. The village government has shown progress in implementing the principles of good governance and village development management. In conclusion, the effectiveness of the use of Village Funds in Mengkait Village has reached a fairly good level. To increase effectiveness in the future, it is recommended to increase the capacity of village officials, strengthen the monitoring and evaluation system, and actively participate of the community in all stages of Village Fund management.